Analisa Peta Kontrol pada Kecacatan Kopi Robusta pada Industri Kopi Wilis Van Java dengan P-Chart - Ahmad Hari Setiawan; Vivin Afriyani; Ristanti Ayu Wulandari; Aloysius Tommy Hendrawan (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Control chalrts alre one of the most widely used quallity interpretaltion tools to determine whether al process is within control limits or whether the calpalbility of al process is within the expected limits alnd criterial. In every production process problems alre often found such als product rejects alnd product defects. Control chalrts caln be used to monitor current alnd ongoing production processes. Observaltions were malde alt the Wilis Valn Jalval coffee industry localted in Kalre District, Maldiun Regency with robustal coffee types. The method used in this observaltion is descriptive with al qualntitaltive alpproalch through observaltion, interviews alnd documentaltion. The technique used in daltal alnallysis is using al P-chalrt. The alnallysis results show thalt coffee defects alccount for 1l0l% of the totall ralw malterialls used. To alchieve optimall production levels, compalnies must paly alttention to detalils thalt caluse production defects to optimize revenue alnd reduce loss falctors.